EFEKTIFITAS PEMBERIAN COKLAT KELOR (Kokoa Moringa Oleifera) TERHADAP KADAR HEMOGLOBIN REMAJA PUTRI - Nurul Hidayah (Jurnal Delima Harapan, 2022)
Iron deficiency anemia is still a major nutritional problem in adolescents in Indonesia. One of the efforts to handle it is by giving Moringa chocolate. Research objective: analyzeeffectiveness of giving Moringa chocolate on hemoglobin levels of adolescent girls. Research method: Type of researchquasi experiment with nonrandomized pretest and posttest design with control group. The population of this study was 75, purposive sampling with a sample of 60 which were divided into a treatment group of 30 people, and a control group of 30 people. The control group consumed 50g of Moringa chocolate for 30 consecutive days, and the control group did not consume Moringa chocolate. Hb levels were measured before and after treatment. Data analysis used paired t-test and independent t-test. Results: Paired t-test in the treatment group p value of 0.009 (p <0.05),CI95%, which means there is a difference in Hb levels before and after being given Moringa chocolate, while in the control group the p value is 0.255 (p>0.05) 95% CI, which means there is no difference in Hb levels in the control group who are not given Moringa chocolate. . Independent analysis of t-test obtained p value of 0.005 (p <0.05), which means that there is a significant effect on the measurement results of post-test HB levels between the treatment group and the control group. Conclusion: Moringa chocolate affects young women's Hb levels.